LOCAL APPLICATION OF RECOMBINANT INTERFERON-ALFA2 FOR TREATMENT OF RECURRENT RESPIRATORY PAPILLOMATOSIS - M. Plouzhnikov (SPb RAACI, 2014)
Abstract. Recurrent respiratory papillomatosis (RRP) is the most frequently occurring tumour of the upper airways associated with a human papilloma virus (HPV). The aim of this study was to reveal some features of systemic and local immunity in RRP, to investigate clinical and immunological efficiency of local treatment with recombinant interferon-α (rIFNα), and to determine clinical and laboratory indications to it’s administration. The study included forty-one patients with confirmed RRP. Their examination included histological examination of papillomas, detection of HPV DNA in papilloma tissues using PCR technique, phenotyping of circulating lymphocytes (CD3+, CD4+, CD8+, CD25+, HLA-DR+) by means of flow cytometry. The levels of IFNγ, TNFα, GM-CSF, IL-2, IL-4, IL-5, IL-10, IL-12, IL-13 in laryngeal secretions were quantified by a multiplex immunoassay. In all cases, we revealed an initially decreased functional activity of Т-lymphocytes, as well as low contents of Т-killer and NK-cells. In laryngeal secretions, increased values of Th1-type-specific cytokines (IFNγ and TNFα) were found. Besides that, high levels of local IL-4 were detected thus being typical to alternative Th2-type response. Single inhalations 1000 000 ME of «Interal» or «Roferon» preparations were administered daily (a total of 10-15 millions ME per therapeutic course). Thirteen patients received the treatment after surgery, as an adjuvant therapy, and eleven patients underwent monotherapy. Complete tumor regression of tumors following this monotherapy was observed in 45,5% of the patients, whereas partial regression was registered in 45%. The effect was mostly expressed in frequently recurring juvenile papillomatosis with aggressive course and histological pattern of actively proliferating papilloma. In the patients with complete tumor regression, high initial levels of TNFα and IL-4/IFNг ratios were revealed initially in laryngeal secretions. When rIFNб was administered, an increase in Th1-type cytokines (IFNγ, IL-12, IL-2) and GM-CSF were revealed, as well as decrease of initially high levels of IL-10, like as lowered levels of IL-4 and IL-13. In cases of partial tumor regression, the levels of IFNα, IL-12, IL-2 and GM-CSF were decreased against initial values, and in the course of treatment they fluctuated within normal reference values. Cancellation of the therapy was followed by increase in IL-4 and IL-13 levels. Hence, the local rIFNα therapy is effective in controlling aggressive recurrent respiratory papillomatosis. Initial increase in TNFα and IL-4/IFNγ ratios in laryngeal secretions may be considered as favorable predictor of anticipated therapy, whereas increased levels of IFNα, IL-2 and IL-12 together with decrease (normalization) of IL-4/IFNγ ratio may reflect the efficiency of the treatment performed.